2017
DOI: 10.1021/acs.inorgchem.7b02436
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer Mechanisms and Optical Thermometry of BaMgF4:Yb3+,Er3+ Phosphor

Abstract: Motivated from our previous studies on the upconversion properties of BaMgF:Yb,Tb phosphor, here we investigated the upconversion properties of BaMgF:Yb,Er phosphor. We demonstrate a two-way versatile approach for the fine-tuning of emission from green to the red region, by varying the dopant concentration and adjusting the pulse width of an infrared laser. The mechanism involved in tuning the emission color by laser power and pulse width variation was illustrated in detail. The temperature dependent upconvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Based on the obtained results we proposed the use of this phosphor as a solar spectrum convertor in perovskite solar cells [13]. We also showed that the same host doped with Yb 3þ -Er 3þ pair can be used in optical thermometry [14]. The rare-earth ion doped UC phosphors are remarkably efficient in transferring the excited state energy of the sensitizer (Yb 3þ ) to the neighboring activators (Tm 3þ or Er 3þ ) which gives rise to an efficient UC emission by the non-linear anti-stokes process [15].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on the obtained results we proposed the use of this phosphor as a solar spectrum convertor in perovskite solar cells [13]. We also showed that the same host doped with Yb 3þ -Er 3þ pair can be used in optical thermometry [14]. The rare-earth ion doped UC phosphors are remarkably efficient in transferring the excited state energy of the sensitizer (Yb 3þ ) to the neighboring activators (Tm 3þ or Er 3þ ) which gives rise to an efficient UC emission by the non-linear anti-stokes process [15].…”
Section: Introductionmentioning
confidence: 85%
“…Recently, we studied the UC properties of BaMgF 4 doped with Yb 3þ , Tb 3þ13 and Yb 3þ , Er 3þ [14]. In both these phosphors we obtained a characteristic emission of Tb 3þ and Er 3þ .…”
Section: Introductionmentioning
confidence: 98%
“…10 As no power threshold was observed in the range of this study, the PA mechanism can be neglected. With the energy diagram constructed in Figure 6C, the process of UC luminescence may be described as follows: (1) The Yb 3+ electrons are excited from 2 F 7/2 ground state to 2 , and the other part decays to the 5 F 5 state via nonradiative relaxation (NR; 5 F 4 / 5 S 2 ~ 5 F 5 ), followed by radiative relaxation to the 5 I 8 ground state to generate the ~ 654 nm red emission ( 5 F 5 → 5 I 8 ). The very weak red luminescence ( Figure 6A) may indicate that the probability of 5 F 4 / 5 S 2 ~ 5 F 5 NR is rather low.…”
Section: Characterizationsmentioning
confidence: 99%
“…Upconversion (UC) luminescence attracted considerable attention during the past decades and is now being applied in the various fields of optical imaging, temperature sensing, solid state lasers, photodynamic therapy, in vitro/in vivo bioimaging, biological labels, photovoltaics and photocatalysis . Trivalent rare‐earth ions (RE 3+ , except for Ce 3+ ) generally exhibit weak electron‐phonon coupling and sharp f‐f transitions due to the shielding effect of neighboring 5s 2 and 5p 6 subshells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation